Impact of BMI and smoking in adolescence and at the start of pregnancy on birth weight - Rebecka Bramsved; Staffan Mårild; Maria Bygdell; Jenny M. Kindblom; Ingela Lindh (BMC, 2023)
Abstract Background Birth weight is an indicator of intra-uterine conditions but also a determinant for future health. The importance of preconception health for a healthy birth weight has been emphasized, but evidence is lacking on how modifiable factors in adolescence, such as body mass index (BMI) and smoking, affect future pregnancy outcome. We evaluated associations between BMI and smoking in adolescence and at the start of pregnancy and birth weight of the first-born child. Methods This longitudinal study included 1256 mothers, born 1962-1992, and their first-born children, born between 1982-2016. Self-reported questionnaire information on weight, height and smoking at age 19 was cross-linked with national register data obtained at the start of pregnancy and with the birth weights of the children. Univariable and multivariable linear regressions were performed to determine the impact of maternal factors at 19 years of age and at the start of the pregnancy respectively, and the importance of BMI status at these points of time for the birth weight of the first child. Results BMI and smoking at the start of the pregnancy displayed strong associations with birth weight in a multivariable analysis, BMI with a positive association of 14.9 g per BMI unit (95% CI 6.0; 23.8 p = 0.001) and smoking with a negative association of 180.5 g (95% CI -275.7; -85.4) p = 0.0002). Smoking and BMI at 19 years of age did not show this association. Maternal birth weight showed significant associations in models at both time-points. Becoming overweight between age 19 and the start of the pregnancy was associated with a significantly higher birth weight (144.6 (95% CI 70.7;218.5) p = 0.0002) compared to mothers with normal weight at both time points. Conclusions Our findings indicate that the time period between adolescence and first pregnancy could be a window of opportunity for targeted health promotion to prevent intergenerational transmission of obesity.